Combination of ROC and MFEP to Determine the Best Web Designer - Eldo, Handry; Marbun, Nasib; Rozi, Ahmad (Cattleya Darmaya Fortuna, 2023)
This research aims to solve the problem of decision making in determining the Best Web Designer. The data collection technique used in this research is literature study. The method that the author applies is ROC as a method of weighting factor weight values and MFEP as a method of determining alternative ranking results. The results of applying a combination of the ROC method and the MFEP method in this study show that A1 (0.447757) is an alternative that has the highest value compared to 4 (four) other alternatives, namely A4 (0.426882), A2 (0.357889), A5 (0.343861), and A3 (0.239611). So it can be concluded that A1 (0.447757) is the most recommended alternative to be chosen as the best web designer in this study.